Teaching therapy decision-making to medical students: a prospective mixed-methods evaluation of a curricular innovation - Diego Garcia-Huidobro; Joaquín Fernandez; Pilar Espinosa; Nicole Lustig; Ignacio Perez; Luz M. Letelier (BMC Medical Education)
Abstract Background Therapy decision-making (TDM) is an essential medical skill. However, teaching therapeutic reasoning poses significant challenges. We present a comprehensive TDM course for medical students and report on student satisfaction with the educational strategies, their perceived importance of various TDM domains, and their self-efficacy in incorporating these elements into clinical decisions. Methods Three student cohorts participated in a 16-week TDM course, which included self-instruction modules, application assignments, faculty symposia, and application seminars as educational strategies. The course focused on TDM and emphasized how factors such as the patient’s diagnosis, needs and preferences, treatment options, physicians’ viewpoints, the patient-physician relationship, and contexts of medical practice impact TDM. After the course, students completed a before-and-after survey assessing their satisfaction with the educational strategies, their perceived importance of ten TDM domains, and their ability to incorporate these domains into patient management. Scores ranged from 1 to 10. Students from the first two cohorts completed a 1- and 2-year follow-ups. Results A total of 387 students completed the course. All educational strategies were well-received, with self-instruction modules and faculty symposia yielding the highest satisfaction rates (94.8% and 88.6% respectively). Before-and-after evaluations indicated that students` perceived importance of the TDM domains increased from an average of 8.0 ± 2.4 at baseline to 9.9 ± 1.0 after the course. Additionally, their perceived ability to integrate TDM domains into practice rose from an average of 5.2 ± 3.2 to 9.4 ± 1.5 by the end of the course. Follow-up results showed a decrease in these outcomes over time. Conclusion This course serves as a successful model for systematically teaching TDM to medical students.